2015
DOI: 10.1101/gad.259341.115
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cells communicate via intercellular protein transfer

Abstract: Mammalian cells mostly rely on extracellular molecules to transfer signals to other cells. However, in stress conditions, more robust mechanisms might be necessary to facilitate cell-cell communications. Cellular senescence, a stress response associated with permanent exit from the cell cycle and the development of an immunogenic phenotype, limits both tumorigenesis and tissue damage. Paradoxically, the long-term presence of senescent cells can promote tissue damage and aging within their microenvironment. Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 60 publications
3
124
1
1
Order By: Relevance
“…It was by studying cell senescence in vitro that the SASP was identified [92], and the ability of senescent cells to induce senescence in surrounding cells [93], both through secreted SASP factors and potentially through direct cell-cell contacts [94].…”
Section: Human Cells and Cell Senescencementioning
confidence: 99%
“…It was by studying cell senescence in vitro that the SASP was identified [92], and the ability of senescent cells to induce senescence in surrounding cells [93], both through secreted SASP factors and potentially through direct cell-cell contacts [94].…”
Section: Human Cells and Cell Senescencementioning
confidence: 99%
“…2 CBs, which in some conditions are called tunneling nano- tubes, are open on both edges and allow transfer of cytoplasmic content to neighboring cells. Interestingly, we also identified mitochondria and lysosomes in CBs, implying that organelles might be transferred between the cells.…”
Section: Senescent Cells Talk Frankly With Their Neighborsmentioning
confidence: 99%
“…4,6 We have recently demonstrated that in addition to secretion, senescent cells affect neighboring cells by direct intercellular protein transfer (IPT). 2 Proteins from senescent cells are directly transferred to recipient neighboring cells, such as immune and cancer cells, triggering activation of signaling pathways in these cells, ultimately leading to changes in cellular behavior.…”
Section: Senescent Cells Talk Frankly With Their Neighborsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells secrete a plethora of pro-inflammatory factors that might aid their removal by the immune system. [1][2][3] However, at advanced age senescent cells gradually accumulate in tissues and the secretory phenotype promotes a chronic "sterile" inflammation which is a hallmark of unhealthy aging. Elimination of senescent cells in mice by a genetic approach led to a decreased burden of age-related disorders, and an increased median survival of the mice.…”
mentioning
confidence: 99%